WATAK TOKOH PROTAGONIS DALAM FILM KARTINI KARYA HANUNG BRAMANTYO (ANALISIS STRUKTURAL) - Supriyati Supriyati; Fitria Wulandari (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research is aimed at describing the protagonist character in the film Kartini by  Hanung Bramantyo. This research is descriptive. The result of the research shows that: (1) the aspect of generosity found in the novel Kartini which means that she likes to give a help to other people. (2) the aspect of honesty found in the character Kartini who likes to be honest to other people. (3) the aspect of sincerity which means that she likes to be sincere towards people who give her compliments as if she is not a person with reputation while she is. (4) the aspect of smart in which she always knows how to make a decision to solve problems. (5) the aspect of independence in which she always tries to send scholarship proposal to continue her study in Netherlands without bothering others. (6) the aspect of loyalty to friends in which she (7) the aspect of defence in which she always defends and fights for woman’s and she is brave to say the truth whenever she faces problems. Based on the result of the analysis, it can be found that the most dominant aspect is sincerity and defend. Meanwhile the less dominant aspect is generosity and independence.